Anaemia in acute coronary syndrome: a cross-sectional study - Khan, Muhammad Dilawaer; Qazi, Jahan Tab; Maqsood, Hamza; Qazi, Shaheryar; Irshad, Khurram; Shakeel, Hassan Abdullah (International Journal of Research in Medical Sciences, 2019)
Background: Acute coronary syndromes (ACS) are an imbalance between myocardial oxygen supply and demand, and the presence of anaemia further potentiates this imbalance. The burden of anaemia in patients presenting with acute coronary syndromes (ACS) is significant. Anaemia has the potential to worsen myocardial ischemic insult by decreasing the oxygen content of the blood supplied to the jeopardized myocardium. Present study investigates the prevalence of anaemia in ACS patients attending a tertiary health care institute. Methods: A total of 148 patients with ACS were recruited in the study from July 2018 to October 2018 in Multan institute of cardiology, Pakistan. All patients were subjected to a detailed history and thorough clinical examination and investigations after obtaining informed consent. Patient having any other diseases known to cause anaemia were excluded. Results: Mean age of patients was 49 years. Out of 148, 114 (77%) were males and 34(23%) were females. Prevalence of anaemia was 38% in Male and 58.8% in Female. Among Male, 18.8% were microcytic, 4.54% were macrocytic and 77.27% were normocytic. Among Female, 50% were microcytic and 50%% were normocytic. Prevalence of ACS was higher is patients with diabetes and hypertension combined (31%) than in patient with diabetes alone (17.56%) or hypertension alone (21.62%). 13.51% were pure vegetarians while 78.37% were on mixed diet consisting of vegetables+meat+pulses. Conclusions: Higher incidence of anaemia was reported in subjects having acute coronary syndrome. Incidence of anaemia in STEMI patients was greater than NSTEMI and unstable angina patients. Severe form of acute coronary syndrome i.e. STEMI was associated with higher incidence of anaemia.